Reconnecting Culture And Resilience: Understanding Minangkabau Women Strategies In Disaster Management - Lengga Pradipta (Universitas Andalas, 2020)
West Sumatra province is the homeland of Minangkabau ethnic group, which possess a strong adat and Islamic value principle; ”adat basandi syara’, syara’ basandi kitabullah” and also prioritizing women as the key person in clan (suku). Aside from its cultural and religious aspects, this province is also prone to disasters. These disasters are directly impacted on Minangkabau people’s livelihood, especially women. In Minangkabau society, women have a crucial role because they are the leader of Rumah Gadang (big house owned by community). This situation puts women as the problem – solver in any occasion, especially when it comes to disaster issues. The aim of this study is to understand the resilience of Minangkabau's women, which focused on their coping strategies at pre, during and post disaster, and how the local knowledge will be applied in this condition. This study used a qualitative methods; observation, in-depth interviews (with local leaders and Bundo Kanduang) and also used secondary data. The findings depict some strategies could be taken by women at disasters, including; mamagang sawah (organizing the paddy field activity) and also badoncek (an ancient tradition which similar with arisan). Those strategies showed a strong connection between women, traditional practice and resilience.